KONSEP DAN PRAKTEK MENGEMBANGKAN KESEIMBANGAN BATIN DALAM AJARAN AGAMA BUDDHA: The Concept and Practice of Developing Inner Balance in Buddhism - Arif Muzayin Shofwan (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Buddhism teaches the concept and practice of developing the mind to achieve true happiness. This qualitative research, conducted through a literature review, examines the concept and practice of developing the mind in Buddhism. The data analysis technique used content analysis, selecting items that align with the research objectives. This research found that the concept of developing equanimity is crucial for facing all of life's problems. To practice equanimity (upekha), one can train oneself to overcome three traits that conflict with equanimity: attachment, indifference, anger, and ill will. The practice of equanimity can be directed at three things: (1) overcoming attachment to loved ones through meditation on impermanence; (2) overcoming indifference to strangers who are neither friends nor enemies through meditation on arousing loving-kindness (metta); and (3) overcoming anger and ill will toward those who harm others by contemplating the causes and conditions of their harmful actions.